2009
DOI: 10.1073/pnas.0805165106
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt/β-catenin signaling is required for CNS, but not non-CNS, angiogenesis

Abstract: Despite the importance of CNS blood vessels, the molecular mechanisms that regulate CNS angiogenesis and blood−brain barrier (BBB) formation are largely unknown. Here we analyze the role of Wnt/β-catenin signaling in regulating the formation of CNS blood vessels. First, through the analysis of TOP-Gal Wnt reporter mice, we identify that canonical Wnt/β-catenin signaling is specifically activated in CNS, but not non-CNS, blood vessels during development. This activation correlates with the expression of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
833
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 640 publications
(869 citation statements)
references
References 32 publications
(35 reference statements)
34
833
1
1
Order By: Relevance
“…Comparative microarray analysis has identified that effectors of Wnt/b-catenin signaling, including Lef1, Apcdd1, and tnfrsf19, are enriched CNS ECs compared to ECs in peripheral organs (Daneman et al 2009(Daneman et al , 2010a. Transgenic reporter mice have confirmed that Wnt/ b-catenin signaling is activated in CNS ECs during embryonic angiogenesis (Liebner et al 2008;Stenman et al 2008;Daneman et al 2009).…”
Section: Regulation Of Barrier Properties During Angiogenesismentioning
confidence: 93%
See 4 more Smart Citations
“…Comparative microarray analysis has identified that effectors of Wnt/b-catenin signaling, including Lef1, Apcdd1, and tnfrsf19, are enriched CNS ECs compared to ECs in peripheral organs (Daneman et al 2009(Daneman et al , 2010a. Transgenic reporter mice have confirmed that Wnt/ b-catenin signaling is activated in CNS ECs during embryonic angiogenesis (Liebner et al 2008;Stenman et al 2008;Daneman et al 2009).…”
Section: Regulation Of Barrier Properties During Angiogenesismentioning
confidence: 93%
“…Comparative microarray analysis has identified that effectors of Wnt/b-catenin signaling, including Lef1, Apcdd1, and tnfrsf19, are enriched CNS ECs compared to ECs in peripheral organs (Daneman et al 2009(Daneman et al , 2010a. Transgenic reporter mice have confirmed that Wnt/ b-catenin signaling is activated in CNS ECs during embryonic angiogenesis (Liebner et al 2008;Stenman et al 2008;Daneman et al 2009). Different Wnt ligands are secreted by neural stem cells and neural progenitors in spatially distinct regions, notably Wnt7a and Wnt7b in ventral regions and Wnt1, Wnt3, Wnt 3a, and Wnt4 in dorsal regions (Stenman et al 2008;Daneman et al 2009).…”
Section: Regulation Of Barrier Properties During Angiogenesismentioning
confidence: 93%
See 3 more Smart Citations